2023
DOI: 10.1101/2023.05.22.541477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term optical imaging of the spinal cord in awake, behaving animals

Abstract: Advances in optical imaging approaches and fluorescent biosensors have enabled an understanding of the spatiotemporal and long-term neural dynamics in the brain of awake animals. However, methodological difficulties and the persistence of post-laminectomy fibrosis have greatly limited similar advances in the spinal cord. To overcome these technical obstacles, we combinedin vivoapplication of fluoropolymer membranes that inhibit fibrosis; a redesigned, cost-effective implantable spinal imaging chamber; and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…2 ); (iii) surgical procedures are more complex and hence require more training than brain procedures; (iv) the spinal cord has a smaller tool builder community than the brain, and advancements happen at slower pace; (v) in general the longevity of spinal cord window implants is lower than for the brain; (vi) the highly-mobile structure of the spinal cord makes it challenging to design implants cable of withstanding traditional restraint paradigms used for brain imaging, limiting the complexity and number of experimental trials that can be performed under awake spinal restraint. 58…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 ); (iii) surgical procedures are more complex and hence require more training than brain procedures; (iv) the spinal cord has a smaller tool builder community than the brain, and advancements happen at slower pace; (v) in general the longevity of spinal cord window implants is lower than for the brain; (vi) the highly-mobile structure of the spinal cord makes it challenging to design implants cable of withstanding traditional restraint paradigms used for brain imaging, limiting the complexity and number of experimental trials that can be performed under awake spinal restraint. 58…”
Section: Resultsmentioning
confidence: 99%
“…66 Also, treating an implant with gradually releasing anti-inflammatory agents might increase the duration of single-cell resolved imaging by suppressing fibrosis. 58 Besides surgical preparation, habituation of the animal remains an equally important factor in maintaining spinal cord window quality when it comes to awake behavior. We found that high mobility of the spinal cord makes it more prone to injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mechanical pinch) (NS) or wide dynamic range (WDR) cells, which encode input from both low‐ and high‐intensity modalities (see William & Coggeshall, 2003). Importantly, adult cutaneous receptive fields are not fixed but are subject to rapid changes in response to contextual factors, such as stimulus history, supraspinal connections and anaesthesia (Ahanonu et al., 2023; Dubner & Ruda, 1992; Sandkühler, 2009). Such flexibility is made possible by the presence of subliminal inputs surrounding a receptive field, which might or might not be recruited over minutes, depending on nearby events (Woolf & King, 1990), controlled by inhibitory circuits within the dorsal horn (Sivilotti & Woolf, 1994; Zeilhofer et al., 2012).…”
Section: Introductionmentioning
confidence: 99%